Polymer-coated magnetic nanoparticles and polymer nanoparticles for the treatment of Mycobacterium tuberculosis (Mtb) - Smit, Marica (Stellenbosch : Stellenbosch University, 2022)
Thesis (PhD)--Stellenbosch University, 2022.